Feline Diaphyseal Fractures: Management and treatment options. Issue 7 (July 2022) - Zurita, Maria; Craig, Andrew
Practical relevance: Cats frequently present with diaphyseal fractures, which require treatment in order to achieve a good return to function. These fractures often occur due to significant trauma; for example, as a result of road traffic accidents, high-rise syndrome and dog bite wounds. The first priority is to ensure the patient is systemically well before embarking on any specific surgical treatment of a fracture. Clinical challenges: Surgical management of diaphyseal fractures can be challenging due to the surgical approach for some bones being technically demanding, for example because of the presence of important neurovascular structures, and the small size of feline bones, which limits the choice of implant size and strength. Further, it may be difficult to visualise fracture alignment when using minimally invasive techniques, although the use of intraoperative fluoroscopy can aid with this, and malalignment can be common for some fracture repairs, particularly in cases where anatomical reconstruction is not possible. Aims: This review focuses on diaphyseal long bone fractures and aims to assist decision-making, with an overview of the management and treatment options available. Evidence base: Many textbooks and original articles have been published on aspects of managing fractures in small animals. The authors also provide recommendations based upon their own clinical experience.